Scaffold-Based Gene Therapeutics for Osteochondral Tissue Engineering - Yan, Xin; Chen, You-Rong; Song, Yi-Fan; Yang, Meng; Ye, Jing; Zhou, Gang; Yu, Jia-Kuo (Frontiers in Pharmacology, 2020)
Significant progress in osteochondral tissue engineering has been made for biomaterials designed to deliver growth factors that promote tissue regeneration. However, due to diffusion characteristics of hydrogels, the accurate delivery of signaling molecules remains a challenge. In comparison to the direct delivery of growth factors, gene therapy can overcome these challenges by allowing the simultaneous delivery of growth factors and transcription factors, thereby enhancing the multifactorial processes of tissue formation. Scaffold-based gene therapy provides a promising approach for tissue engineering through transfecting cells to enhance the sustained expression of the protein of interest or through silencing target genes associated with bone and joint disease. Reports of the efficacy of gene therapy to regenerate bone/cartilage tissue regeneration are widespread, but reviews on osteochondral tissue engineering using scaffold-based gene therapy are sparse. Herein, we review the recent advances in gene therapy with a focus on tissue engineering scaffolds for osteochondral regeneration.